Cyclisation Reactions Involving Alkyl Enol Ethers. Issue 23 (12th September 2019) - Lempenauer, Luisa; Lemière, Gilles; Duñach, Elisabet
Abstract: Enol ethers are a fascinating product class and valuable building blocks with versatile reactivities and synthetic applications. With the emergence of silyl enol ethers, the chemistry of simple alkyl enol ethers has received less attention and targeted reviews of their chemistry are scarce. Especially intramolecular reactions under participation of an enol ether function have never been specifically surveyed. The construction of cyclic scaffolds is arguably one of the most important and challenging tasks of the organic chemist and intramolecular cyclisations represent the most straight‐forward tool to achieve this goal. The potential of enol ether‐containing substrates to form oxygenated carbo‐ and heterocycles is obvious. The purpose of this review is to discuss their particular reactivity and to direct the reader's attention to how their unique properties have been harnessed by organic chemists for the construction of rings. Abstract :